Pyrrosia sarthalensis, a new species of Polypodiaceae from Kathua District, Jammu and Kashmir, Western Himalaya, India - Singh, Sumit; Sneha; Singh, Bikarma (Phytotaxa, 2021)
Pyrrosia sarthalensis, belonging to the family Polypodiaceae from the Bani Valley of Kathua district, Himalayan Jammu & Kashmir, India is described here as a new species. It shows restricted distributional range and so far, is only known from the Bani Valley, within the Himalayan centre of endemism. It is an epiphytic fern species having brownish sori, formed only on the upper half of the frond. Other diagnostic features include grooved rhizomes, rhizome scales, lamina size and structure, sori placement, size and structure, and spore characters. This new species is morphologically similar to P. flocculosa but differs in certain characters.